Study of Acute Toxicity and Irritant Effect of Nasal Spray Naltrexone Hydrochloride - Yu. M. Domnina; V. V. Suslov; S. A. Kedik; D. A. Akhmedova; A. P. Malkova (Разработка и регистрация лекарственных средств)
Introduction. Acute toxicity of naltrexone hydrochloride nasal spray during intragastric administration to mice and local irritant effect on rabbits was studied. At all stages of the experiment, observations were made on the General condition of the animals. The state of homeostasis was evaluated using functional, hematological and morphometric methods. According to the results of research, there was no local irritant effect on the eyes of rabbits, as well as no toxic effect of high doses of the drug on animals. Introduction. Naltrexone hydrochloride in doses of 1.5– 5 mg/day has shown its effectiveness in the treatment of a number of diseases. Due to the lack of such a "low-dose" naltrexone registered on the pharmaceutical market, we have developed the composition of the nasal spray naltrexone hydrochloride. One of the stages of our research is to study the safety of the drug being developed. The first step in this direction was to study its acute toxicity and local irritant effect.Aim. Study of acute toxicity and local irritant effect of naltrexone hydrochloride nasal spray.Materials and methods. The object of the study was a nasal spray of naltrexone hydrochloride. Acute toxicity studies were performed on outbred adult mice (females). Study of local irritant effect on Soviet chinchilla rabbits (males).Results and discussion. The study of acute toxicity showed that the drug, at a dose significantly higher than the estimated maximum daily therapeutic dose for humans, did not have a significant toxic effect on the body of laboratory animals. The presence of a local irritant effect in the studied drug was not established in the framework of the experiment.Conclusion. As part of the experiment, the drug under study did not have a local irritant or toxic effect on the animal body. The results obtained allow us to continue the development and study of the nasal spray naltrexone hydrochloride.